Targeting the Tumor Microenvironment: A Literature Review of the Novel Anti-Tumor Mechanism of Statins - Zhu, Peng-Fei; Wang, Ming-Xing; Chen, Zhe-Ling; Yang, Liu (Frontiers in Oncology, 2021)
Statins is widely used in clinical practice as lipid-lowering drugs and has been proven to be effective in the treatment of cardiovascular, endocrine, metabolic syndrome and other diseases. The latest preclinical evidence shows that statins have anti-proliferation, pro-apoptotic, anti-invasion and radiotherapy sensitization effects on tumor cells, suggesting that statins may become a new type of anti-tumor drugs. For a long time, mevalonate pathway has been proved to play a supporting role in the development of tumor cells. As an effective inhibitor of mevalonate pathway, statins have been proved to have a direct auxiliary anti-tumor effect in a large number of studies. In addition, anti-tumor effects of statins through ferroptosis, pyroptosis, autophagy and tumor microenvironment (TME) have also been gradually discovered. However, the specific mechanism of the antitumor effect of statins in the tumor microenvironment has not been clearly elucidated. Herein, we reviewed the antitumor effects of statins in tumor microenvironment, focusing on hypoxia microenvironment, immune microenvironment, metabolic microenvironment, acid microenvironment and mechanical microenvironment.